2016
DOI: 10.3233/jad-160047
|View full text |Cite
|
Sign up to set email alerts
|

Intraneuronal Amylin Deposition, Peroxidative Membrane Injury and Increased IL-1β Synthesis in Brains of Alzheimer’s Disease Patients with Type-2 Diabetes and in Diabetic HIP Rats

Abstract: Amylin is a hormone synthesized and co-secreted with insulin by pancreatic β-cells that crosses the blood-brain barrier and regulates satiety. Amylin from humans (but not rodents) has an increased propensity to aggregate into pancreatic islet amyloid deposits that contribute to β-cell mass depletion and development of type-2 diabetes by inducing oxidative stress and inflammation. Recent studies demonstrated that aggregated amylin also accumulates in brains of Alzheimer’s disease (AD) patients, preponderantly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 41 publications
3
90
0
Order By: Relevance
“…Interestingly, IAPP is found in both the parenchyma and blood vessels of patients with AD who do not carry a diagnosis of T2D in about the same concentrations as subjects with only T2D . While IAPP in the aforementioned study was found extracellularly, a follow‐up investigation used immunohistochemistry to demonstrate IAPP within neurones themselves, found in the absence of mRNA, excluding production of IAPP by the neurones . A small study of five persons with ADNC and six controls found IAPP inclusions in the pericytes, cells involved with the BBB (discussed below), around the hippocampus and parahippocampal cortex .…”
Section: Amylin the Blood‐brain Barrier And Lymphaticsmentioning
confidence: 95%
“…Interestingly, IAPP is found in both the parenchyma and blood vessels of patients with AD who do not carry a diagnosis of T2D in about the same concentrations as subjects with only T2D . While IAPP in the aforementioned study was found extracellularly, a follow‐up investigation used immunohistochemistry to demonstrate IAPP within neurones themselves, found in the absence of mRNA, excluding production of IAPP by the neurones . A small study of five persons with ADNC and six controls found IAPP inclusions in the pericytes, cells involved with the BBB (discussed below), around the hippocampus and parahippocampal cortex .…”
Section: Amylin the Blood‐brain Barrier And Lymphaticsmentioning
confidence: 95%
“…Anti-mouse or anti-rabbit IgG (1:50, A3562, A3687, Sigma, MO) were secondary antibodies. The specificity of the amylin antibody in both human and rat brain tissues was established in previous studies 6,7,29 .…”
Section: Methodsmentioning
confidence: 99%
“…Tissues were processed as previously described. 6,29 Antibodies against amylin (1:200, T-4157; Bachem-Peninsula Laboratories, San Carlos, CA), glial fibrillary acidic protein (GFAP; 1:600, MAB360, Millipore), and myelin basic protein (MBP; 1:5,000, AMAB91064, clone CL2829, Sigma) were the primary antibodies. Antimouse or antirabbit IgG (1:50, A3562, A3687, Sigma) were secondary antibodies.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent study has shown that brains of type 2 diabetic patients with AD have IAPP deposits inside the neurons promoting the synthesis of proinflammatory cytokine interleukin (IL)‐1β and additionally forming adducts with 4‐hydroxynoneal (4‐HNE), a marker of peroxidative membrane injury. These effects were also observed in mice expressing human IAPP or injected with aggregated human IAPP, thus indicating that elevated circulating levels of IAPP directly correlate with neuronal damage induced by oxidative stress and aberrant inflammatory responses, although the mechanisms underlying intracellular IAPP uptake have not been elucidated to this point …”
Section: Amyloidogenesis: a Common Process To Both Pathologiesmentioning
confidence: 99%